Polyetherimide-based high-temperature energy storage composite dielectric material and preparation method thereof

By introducing ferroelectric polymers and nano core-shell particles into the polyetherimide matrix, the composite dielectric film is prepared, which solves the problems of low electric breakdown strength and large dielectric loss of polymer-based dielectric capacitors in high temperature environments, and achieves the effects of high energy storage density and high energy storage efficiency.

CN119899408AActive Publication Date: 2025-04-29XI AN JIAOTONG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510036159.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-29
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The existing polymer-based dielectric capacitors have problems such as low electrical breakdown strength, large dielectric loss, limited dielectric constant and temperature sensitivity in high temperature environments, which limit their application in high temperature environments.

Method used

By introducing ferroelectric polymers and inorganic nanocore-shell particles into the polyetherimide matrix, a composite dielectric film is prepared to improve the high-temperature breakdown field strength and polarization response ability of the energy storage dielectric and reduce dielectric loss.

Benefits of technology

Under high temperature conditions, the prepared composite dielectric film has high energy storage density and high energy storage efficiency, with improved breakdown strength and reduced dielectric loss, and is suitable for high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899408A_ABST
    Figure CN119899408A_ABST
Patent Text Reader

Abstract

The invention discloses a polyetherimide-based high-temperature energy storage composite dielectric material and a preparation method thereof.The preparation method comprises the steps that nano core-shell particles with silicon dioxide coated on the surface of silicon carbide are prepared, and a nano core-shell particle turbid solution is obtained; preparing a polyetherimide solution and a ferroelectric polymer solution; adding a polyetherimide solution and a ferroelectric polymer solution into the nano core-shell particle turbid solution to prepare a composite dielectric solution; and coating the composite dielectric solution on a glass substrate, drying at a series of temperatures, and stripping to obtain the composite dielectric film. The nano core-shell filler has the advantage of wide forbidden band, the insulating property of the material is enhanced, meanwhile, the mechanical property of the material is enhanced through the formed micron-scale and nano-scale phase separation structure, and the breakdown field strength under the high-temperature condition is improved; the polarization response capability of the composite dielectric is enhanced by means of the interfacial effect between the core-shell filler and the polyetherimide matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of dielectric capacitors, can be used in high temperature environments, and is a polyetherimide-based composite dielectric material with added ferroelectric polymer and nano core-shell particles and a preparation method thereof. Background Art

[0002] Polymer-based dielectric capacitors have broad application prospects in smart grids, distributed energy, and hybrid vehicles due to their excellent properties such as high power density, fast charge and discharge efficiency, and long cycle life.

[0003] However, the current mainstream polymer-based materials have the following major problems: 1. The dielectric breakdown strength of the dielectric is low, which limits the upper limit of its operating voltage and energy density; 2. The dielectric loss is large at high frequencies, which will lead to reduced energy conversion efficiency and heat generation; 3. The dielectric constant is limited, which directly affects the electrical energy storage capacity per unit volume; 4. The dielectric properties of polymer materials are sensitive to temperature and fluctuate with temperature, which is not conducive to maintaining stable performance over a wide temperature range, reducing its applicability under extreme environmental conditions.

[0004] Therefore, alleviating electrical breakdown failure due to carrier migration while enhancing the polarization response of the polymer matrix, reducing dielectric loss and improving temperature stability has become one of the hot spots and focuses in the research of high-temperature polymer-based dielectric capacitors.

[0005] Polyetherimide (PEI) has a high glass transition temperature (T g ), in the range of room temperature to 150℃, due to its unique structure, compared with other high T g Dielectric polymer, it shows better thermal stability, better breakdown strength and lower dielectric loss. However, the relative dielectric constant of pure PEI is low. Many studies have improved the dielectric constant of composite materials by adding nano inorganic fillers with high dielectric constant to PEI. For example, "A core-shell structure filler and its preparation method and application in polyetherimide-based energy storage composite dielectric film" disclosed in Chinese patent literature, its publication number is CN117757147A. The invention has prepared a high breakdown strength (485.0kV / mm) at 150°C and a dielectric constant of (10~10 6 Hz) shows almost frequency-independent characteristics and has good frequency stability of dielectric composite materials. However, due to the dielectric difference between the nano-inorganic filler and the polymer composite interface, the breakdown strength of the nano-composite dielectric decreases. Therefore, one of the current problems to be solved is to avoid the charge accumulation at the interface between the inorganic filler and the polymer while improving the energy storage performance. Summary of the invention

[0006] In order to solve the above-mentioned defects existing in the prior art, the purpose of the present invention is to provide a polyetherimide-based high-temperature energy storage composite dielectric material and a preparation method thereof. A composite dielectric film is prepared by introducing ferroelectric polymers and inorganic nano core-shell particles into a polyetherimide matrix, thereby improving the high-temperature breakdown field strength and polarization response of the energy storage dielectric, reducing dielectric loss, and obtaining high energy storage density and energy storage efficiency under high temperature conditions.

[0007] The present invention is achieved through the following technical solutions.

[0008] One aspect of the present invention provides a method for preparing a polyetherimide-based high-temperature energy storage composite dielectric material, comprising the following steps:

[0009] 1) adding nano core-shell particle filler to N-methylpyrrolidone solvent in a mass ratio of 100:(3-12), and ultrasonically treating to obtain a nano core-shell particle turbid solution;

[0010] 2) adding a polyetherimide solution and a ferroelectric polymer solution to the nano core-shell particle turbid solution in a mass ratio of 100:(1-4):(96-99), mixing them evenly, and obtaining a composite dielectric solution;

[0011] 3) The obtained composite dielectric solution is coated on a clean glass substrate, and then peeled off after being dried at a series of temperatures to obtain a composite dielectric film.

[0012] Preferably, the nano core-shell filler is prepared according to the following method:

[0013] The silicon carbide nanoparticles are sintered in a high temperature furnace at 900-1100° C. for 5-6 hours to obtain nano core-shell particle fillers uniformly coated with silicon dioxide.

[0014] Preferably, the particle size of the silicon carbide nanoparticles is in the range of 50 to 100 nm, and the thickness of the outer shell silicon dioxide is 5 to 10 nm.

[0015] Preferably, the polyetherimide solution is an N-methylpyrrolidone solution with a mass concentration of 100 to 150 mg / mL.

[0016] Preferably, the ferroelectric polymer is polyvinylidene fluoride PVDF, polyvinylidene fluoride-co-hexafluoropropylene P (VDF-HFP) or Kramar terpolymer P (VDF-TrFE-CFE.

[0017] Preferably, the ferroelectric polymer solution is prepared as follows:

[0018] The ferroelectric polymer is added into N-methylpyrrolidone solvent and stirred at a temperature of 50 to 80° C. for 8 to 10 hours to obtain a ferroelectric polymer solution with a concentration of 180 to 210 mg / mL.

[0019] Preferably, the nano core-shell filler is added to the N-methylpyrrolidone solvent, and ultrasonic treatment is performed using a cutting-edge ultrasonic device, with an ultrasonic power of 600 to 700 W and an ultrasonic time of 10 to 15 hours.

[0020] Preferably, the preparation of the composite dielectric film includes uniformly coating the composite dielectric solution on a glass substrate by a casting method, keeping it warm in an oven preheated to 70°C for 12 to 15 hours, then heating it to 100 to 120°C and keeping it warm for 5 to 8 hours, and then keeping it warm at 150 to 160°C and 200 to 210°C for 12 to 15 hours respectively, to obtain a composite dielectric film.

[0021] Another aspect of the present invention provides a polyetherimide-based high-temperature energy storage composite dielectric material prepared by the method.

[0022] The present invention adopts the above technical solution, which has the following beneficial effects:

[0023] 1. The present invention uses inorganic nanoparticles to prepare core-shell structure fillers, directly oxidizes a certain amount of silicon carbide particles on their surface through high-temperature sintering to generate a silicon dioxide shell layer, and obtains wide-bandgap SiC@SiO2 particles, and then introduces the particles and ferroelectric polymers into a polyetherimide matrix, utilizing the excellent properties of polyetherimide such as high glass transition temperature and low dielectric loss, combined with the wide bandgap advantage of the silicon dioxide shell material in the core-shell nanoparticles, to increase the energy required for carriers to cross the energy barrier, thereby enhancing the insulation performance of the material; at the same time, the nano- and micron-scale phase separation structures generated by the ferroelectric polymer in the polyetherimide matrix improve the mechanical properties of the composite material, thereby improving the breakdown field strength of the polyetherimide at high temperatures.

[0024] 2. Enhance the polarization response ability of the composite dielectric by relying on the interface effect between the core and shell of the core-shell filler and between the filler and the polymer matrix.

[0025] 3. Under the ratio of the present invention, at 150°C, high energy storage density and high energy storage efficiency can be obtained simultaneously, wherein high energy storage efficiency can effectively reduce the release of stored energy in the form of heat and extend the service life of the material. The results show that the energy storage density of the prepared composite dielectric film can exceed 5J / cm at 150°C. 3 , energy storage efficiency exceeds 90%.

[0026] 4. The polyetherimide-based composite dielectric of the present invention has a simple preparation process, good stability, can meet different application requirements, involves cheap raw materials, mature technology, and is suitable for industrial production. It can be widely used in high-temperature polymer materials for smart grids, distributed energy, and hybrid vehicles. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The drawings described herein are used to provide a further understanding of the present invention, constitute a part of the present application, and do not constitute an improper limitation of the present invention. In the drawings:

[0028] Figure 1 (a) and Figure 1 (b) are transmission electron microscopy (TEM) images of core-shell SiC@SiO2SiC@SiO2 particles with a size of 5 nm and 20 nm prepared in the embodiments of the present invention;

[0029] Figure 2 (a) and (b) are scanning electron microscope (SEM) and energy dispersive spectrometer (EDS) comparison diagrams of the polyetherimide-based composite dielectric film prepared in Example 2 of the present invention and the polyetherimide dielectric film prepared in the comparative example;

[0030] Figure 3 The composite dielectric films prepared in Examples 1-4 of the present invention and the comparative examples are prepared at room temperature T R Figure (a) and 150℃ figure (b) are the curves of dielectric constant and dielectric loss changing with frequency;

[0031] Figure 4 The composite dielectric films prepared in Examples 1-4 of the present invention and the comparative examples are prepared at room temperature T R Weibull distribution and breakdown field strength diagram at 150℃, (a) and (c) are Weibull distribution diagrams, (b) and (d) are breakdown field strength diagrams;

[0032] Figure 5 The composite dielectric films prepared in Examples 1-4 of the present invention and the comparative examples are prepared at room temperature T R Energy storage density diagram of Figure (a) and 150℃ figure (b). DETAILED DESCRIPTION

[0033] The present invention will be described in detail below in conjunction with the accompanying drawings and specific embodiments. The exemplary embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0034] The embodiment of the present invention provides a method for preparing a polyetherimide-based high-temperature energy storage composite dielectric material, comprising the following steps:

[0035] Step 1, preparing nano core-shell particle turbid solution:

[0036] Silicon carbide nanoparticles with a particle size range of 50-100nm and a shell silicon dioxide thickness of 5-10nm are sintered and kept warm at 900-1100°C in a high-temperature furnace for 5-6 hours to obtain nano core-shell particle fillers uniformly coated with silicon dioxide.

[0037] The nano-core-shell particle filler is added to N-methylpyrrolidone solvent in a mass ratio of 100:(3-12), and the nano-core-shell particle turbid solution is obtained at a power of 600-700 W and ultrasonic treatment is performed for 10-15 hours.

[0038] Step 2, preparing a composite dielectric solution:

[0039] The polyetherimide is added into N-methylpyrrolidone solvent to obtain a polyetherimide solution with a mass concentration of 100 to 200 mg / mL.

[0040] A ferroelectric polymer (polyvinylidene fluoride PVDF, polyvinylidene fluoride-co-hexafluoropropylene P (VDF-HFP) or Kramar terpolymer P (VDF-TrFE-CFE)) is added to an N-methylpyrrolidone solvent and stirred at a temperature of 50 to 80° C. for 8 to 10 hours to obtain a ferroelectric polymer solution with a concentration of 180 to 210 mg / mL.

[0041] The polyetherimide solution and the ferroelectric polymer solution were added to the nano core-shell particle turbid solution in a mass ratio of 100:(1-4):(96-99), and then stirred for 12 hours to mix the three evenly to obtain a composite dielectric solution.

[0042] Step 3, preparing a composite dielectric film:

[0043] The obtained composite dielectric solution is coated on a clean glass substrate, kept in an oven preheated at 70°C for 12 to 15 hours, then heated to 100 to 120°C and kept for 5 to 8 hours, and then kept at 150 to 160°C and 200 to 210°C for 12 to 15 hours respectively, dried and peeled off to obtain a composite dielectric film.

[0044] The present invention is further illustrated by the following examples.

[0045] Example 1

[0046] The method for preparing the polyetherimide-based energy storage composite dielectric film with excellent high-temperature energy storage characteristics in this embodiment comprises the following steps:

[0047] 1) Preparation of core-shell structured SiC@SiO2 particle turbidity:

[0048] 0.1 g of silicon carbide nanoparticles were weighed and put into a crucible. The high-temperature furnace temperature was set at 900° C. and kept warm for 6 h in an air atmosphere to obtain a silicon dioxide shell layer with a thickness of 6 nm, which was recorded as SiC@SiO2.

[0049] SiC@SiO2 particles were added to N-methylpyrrolidone solvent at a mass ratio of 100:6, and ultrasonic treatment was performed using cutting-edge ultrasonic equipment to uniformly disperse the filler in the solvent. The ultrasonic treatment was performed at a power of 600 W for 15 hours to obtain a turbid solution of nano core-shell particles.

[0050] 2) Preparation of polyetherimide solution:

[0051] 200 mg of polyetherimide was added to 1 mL of N-methylpyrrolidone solvent, and stirred at 60° C. for 8 h to obtain a polyetherimide solution with a concentration of 200 mg / mL.

[0052] 3) Preparation of ferroelectric polymer polyvinylidene fluoride (PVDF) solution:

[0053] 200 mg of ferroelectric polymer polyvinylidene fluoride particles were added to 1 mL of N-methylpyrrolidone solvent and stirred at 60° C. for 8 h to obtain a polyvinylidene fluoride solution with a concentration of 200 mg / mL.

[0054] 4) Preparation of composite dielectric solution

[0055] The polyetherimide solution and the ferroelectric polymer solution were added to the nano core-shell particle turbid solution in a mass ratio of 100:1:99, and the mixture was evenly mixed to obtain a composite dielectric solution.

[0056] 5) Preparation of composite dielectric films:

[0057] A glass sheet was used as a substrate, 200 μL of the composite dielectric solution was measured with a pipette, and the composite dielectric solution was evenly coated on the glass sheet by a casting method. The glass sheet carrying the composite dielectric solution was transferred to an oven pre-heated at 70°C for 12 hours, then heated to 100°C for 6 hours, and then heated at 150°C and 200°C for 14 hours respectively, to obtain a composite dielectric film with a thickness of 4 to 6 μm, which was recorded as 0.30SiC@SiO2 / 1PVDF / 99PEI, abbreviated as 1-99.

[0058] Example 2

[0059] 1) Preparation of core-shell structured SiC@SiO2 particle turbidity:

[0060] 0.1 g of silicon carbide nanoparticles were weighed and put into a crucible. The high-temperature furnace temperature was set at 1000° C. and kept warm for 5 h in an air atmosphere to obtain a silicon dioxide shell layer with a thickness of 8 nm, which was recorded as SiC@SiO2.

[0061] SiC@SiO2 particles were added to N-methylpyrrolidone solvent at a mass ratio of 100:10, and ultrasonic treatment was performed using cutting-edge ultrasonic equipment to uniformly disperse the filler in the solvent. The ultrasonic treatment was performed for 10 hours at a power of 650 W to obtain a turbid solution of nano core-shell particles.

[0062] 2) Preparation of polyetherimide solution:

[0063] 150 mg of polyetherimide was added to 1 mL of N-methylpyrrolidone solvent, and the mixture was stirred at 70° C. for 9 h to obtain a polyetherimide solution with a concentration of 150 mg / mL.

[0064] 3) Preparation of ferroelectric polymer polyvinylidene fluoride-co-hexafluoropropylene P (VDF-HFP) solution:

[0065] 180 mg of ferroelectric polymer polyvinylidene fluoride-co-hexafluoropropylene particles were added to 1 mL of N-methylpyrrolidone solvent and stirred at 70° C. for 9 h to obtain a polyvinylidene fluoride-co-hexafluoropropylene solution with a concentration of 180 mg / mL.

[0066] 4) Preparation of composite dielectric solution

[0067] The polyetherimide solution and the ferroelectric polymer solution were added to the nano core-shell particle turbid solution in a mass ratio of 100:2:98, and the mixture was evenly mixed to obtain a composite dielectric solution.

[0068] 5) Preparation of composite dielectric films:

[0069] A glass sheet was used as a substrate, 200 μL of the composite dielectric solution was measured with a pipette, and the composite dielectric solution was evenly coated on the glass sheet by a casting method. The glass sheet carrying the composite dielectric solution was transferred to an oven pre-heated at 70°C for 15 hours, then heated to 120°C for 5 hours, and then heated at 160°C and 210°C for 12 hours respectively. The obtained polyetherimide-based composite dielectric film was recorded as 0.30SiC@SiO2 / 2P(VDF-HFP) / 98PEI, abbreviated as 2-98.

[0070] Example 3

[0071] 1) Preparation of core-shell structured SiC@SiO2 particle turbidity:

[0072] Weigh 0.1 g of silicon carbide nanoparticles and put them into a crucible. Set the high-temperature furnace temperature to 1100° C. and keep it warm for 5.5 h in an air atmosphere to obtain a silicon dioxide shell layer with a thickness of 10 nm, which is recorded as SiC@SiO2.

[0073] SiC@SiO2 particles were added to N-methylpyrrolidone solvent at a mass ratio of 100:12, and ultrasonic treatment was performed using cutting-edge ultrasonic equipment to uniformly disperse the filler in the solvent. The ultrasonic treatment was performed at a power of 700 W for 13 hours to obtain a turbid solution of nano core-shell particles.

[0074] 2) Preparation of polyetherimide solution:

[0075] 150 mg of polyetherimide was added to 1 mL of N-methylpyrrolidone solvent, and stirred at 80° C. for 7 h to obtain a polyetherimide solution with a concentration of 100 mg / mL.

[0076] 3) Preparation of ferroelectric polymer Clamart terpolymer P (VDF-TrFE-CFE) solution:

[0077] 190 mg of ferroelectric polymer Clamard terpolymer particles were added to 1 mL of N-methylpyrrolidone solvent and stirred at 70° C. for 9 h to obtain a Clamard terpolymer solution with a concentration of 190 mg / mL.

[0078] 4) Preparation of composite dielectric solution

[0079] The polyetherimide solution and the ferroelectric polymer solution were added to the nano core-shell particle turbid solution in a mass ratio of 100:3:97, and the mixture was evenly mixed to obtain a composite dielectric solution.

[0080] 5) Preparation of composite dielectric films:

[0081] A glass sheet was used as a substrate, 200 μL of the composite dielectric solution was measured with a pipette, and the composite dielectric solution was evenly coated on the glass sheet by a casting method. The glass sheet carrying the composite dielectric solution was transferred to an oven pre-heated at 70°C for 14 hours, then heated to 110°C for 8 hours, and then heated at 160°C and 205°C for 13 hours respectively. The obtained polyetherimide-based composite dielectric film was recorded as 0.30SiC@SiO2 / 3P(VDF-TrFE-CFE) / 97PEI, abbreviated as 3-97.

[0082] Example 4

[0083] 1) Preparation of core-shell structured SiC@SiO2 particle turbidity:

[0084] Weigh 0.1 g of silicon carbide nanoparticles and put them into a crucible. Set the temperature of the high-temperature furnace and keep it at 1050° C. in an air atmosphere for 6 hours to obtain a silicon dioxide shell layer with a thickness of 6 nm, which is recorded as SiC@SiO2.

[0085] SiC@SiO2 particles were added to N-methylpyrrolidone solvent at a mass ratio of 100:3, and ultrasonic treatment was performed using cutting-edge ultrasonic equipment to uniformly disperse the filler in the solvent. The ultrasonic treatment was performed at a power of 600 W for 12 hours to obtain a turbid solution of nano core-shell particles.

[0086] 2) Preparation of polyetherimide solution:

[0087] 210 mg of polyetherimide was added to 1 mL of N-methylpyrrolidone solvent, and the mixture was stirred at 65° C. for 10 h to obtain a polyetherimide solution with a concentration of 210 mg / mL.

[0088] 3) Preparation of ferroelectric polymer polyvinylidene fluoride (PVDF) solution:

[0089] 210 mg of ferroelectric polymer polyvinylidene fluoride particles were added to 1 mL of N-methylpyrrolidone solvent and stirred at 65° C. for 10 h to obtain a polyvinylidene fluoride solution with a concentration of 210 mg / mL.

[0090] 4) Preparation of composite dielectric solution

[0091] The polyetherimide solution and the ferroelectric polymer solution were added to the nano core-shell particle turbid solution in a mass ratio of 100:4:96, and the mixture was evenly mixed to obtain a composite dielectric solution.

[0092] 5) Preparation of composite dielectric films:

[0093] A glass sheet was used as a substrate, 200 μL of the composite dielectric solution was measured with a pipette, and the composite dielectric solution was evenly coated on the glass sheet by a casting method. The glass sheet carrying the composite dielectric solution was transferred to an oven pre-heated at 70°C for 13 hours, then heated to 105°C for 7 hours, and then heated at 155°C and 200°C for 15 hours respectively, to obtain a composite dielectric film with a thickness of 4 to 6 μm, which was recorded as 0.30SiC@SiO2 / 4PVDF / 96PEI, abbreviated as 4-96.

[0094] Comparative Example

[0095] The difference between this comparative example and Example 1 is that only steps (2) and (5) are performed, 200 mg of polyetherimide is weighed and added to 2 mL of N-methylpyrrolidone solvent, and stirred at 60° C. for 8 h to obtain a 100 mg / mL pure polyetherimide solution. The pure polyetherimide solution is cast on a glass sheet, and the same drying steps are performed to obtain a polyetherimide dielectric film, abbreviated as P-PEI.

[0096] Figure 1 (a) and Figure 1(b) are TEM images of 5 nm and 20 nm core-shell SiC@SiO2 particles prepared in Examples 1-4, respectively, forming a complete core-shell structure and the thickness of the silica shell layer is 6 nm.

[0097] Figure 2 (a) and (b) are surface SEM and EDS comparison diagrams of preferred embodiment 2 of the present invention and the comparative example. The Si, C, O, F and N elements are evenly distributed in the composite dielectric, indicating that SiC@SiO2 is successfully introduced, and the ferroelectric polymer polyvinylidene fluoride forms a nano- and micron-scale phase separation structure inside the polyetherimide. SiC@SiO2 tends to be distributed inside the micron-sized polyvinylidene fluoride (the white circle is the micron-level phase separation structure, and the black circle is the nano-level phase separation structure).

[0098] Figure 3 For Examples 1-4 and Comparative Examples at room temperature T in Figure (a) R Figure (a) and (b) are the curves of dielectric constant and dielectric loss versus frequency at 150°C. It can be seen that for all composite dielectrics, the dielectric constant exhibits good frequency stability within the tested frequency range (100-1MHz). Furthermore, the interface effect between the filler and the polymer matrix enhances the polarization response of the composite dielectric, which helps to improve the dielectric constant.

[0099] Figure 4 For Examples 1-4 and Comparative Examples at room temperature T R Figure (a), (c) Weibull distribution and Figure (b), (d) breakdown field strength at 150℃, by Figure 4 It can be seen that the breakdown strength of the composite dielectric prepared in Example 2 is 658.57 MV / m at room temperature, and the breakdown strength is improved to 718.21 MV / m at 150°C. This is due to the wide bandgap advantage of the shell material in the nano core-shell particles and the enhancement of the mechanical properties of the composite dielectric by the ferroelectric polymer, thereby improving the breakdown strength of the composite dielectric.

[0100] Figure 5 The energy storage density and efficiency diagram of Examples 1-4 of the present invention and the comparative example at room temperature and 150°C are shown in FIG. Figure 5 It can be seen that the discharge energy density of the composite dielectric prepared in Example 2 at room temperature and 625 MV / m is 7.24 J / cm 3 The efficiency reaches 94.6% when the temperature is high; the energy storage density reaches 10J / cm at 150℃ and 700MV / m. 3 , the efficiency at this time is 93.3%. This is mainly due to the improvement of breakdown strength, and the interface effect between the core and shell of the core-shell filler and between the filler and the polymer matrix enhances the polarization response ability of the composite dielectric, thereby improving the energy storage density and energy storage efficiency.

[0101] The core-shell nanoparticles with wide bandgap prepared by the present invention effectively improve the energy barrier of carrier migration through the silicon dioxide shell layer, and generate nano and micron-scale phase separation structures inside the matrix by adding ferroelectric polymers, thereby enhancing the mechanical properties of polyetherimide and effectively improving the breakdown strength of polyetherimide at high temperatures; at the same time, the polarization response is significantly enhanced by relying on the interface polarization mechanism between the filler and the matrix, thereby obtaining a polyetherimide-based composite dielectric with higher energy storage density and energy storage efficiency under high temperature conditions.

[0102] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.

Claims

1. A method for preparing a polyetherimide-based high-temperature energy storage composite dielectric material, characterized in that: The following steps are involved: 1) adding nano core-shell particle filler to N-methylpyrrolidone solvent in a mass ratio of 100:(3-12), and ultrasonically treating to obtain a nano core-shell particle turbid solution; 2) adding a polyetherimide solution and a ferroelectric polymer solution to the nano core-shell particle turbid solution in a mass ratio of 100:(1-4):(96-99), mixing them evenly, and obtaining a composite dielectric solution; 3) The obtained composite dielectric solution is coated on a clean glass substrate, and then peeled off after being dried at a series of temperatures to obtain a composite dielectric film.

2. The method for preparing a polyetherimide-based high-temperature energy storage composite dielectric material according to claim 1, characterized in that: The nano core-shell filler is prepared according to the following method: The silicon carbide nanoparticles are sintered in a high temperature furnace at 900-1100° C. for 5-6 hours to obtain nano core-shell particle fillers uniformly coated with silicon dioxide.

3. The method for preparing a polyetherimide-based high-temperature energy storage composite dielectric material according to claim 2, characterized in that: The particle size of the silicon carbide nanoparticles ranges from 50 to 100 nm, and the thickness of the silicon dioxide in the shell is 5 to 10 nm.

4. The method for preparing a polyetherimide-based high-temperature energy storage composite dielectric material according to claim 1, characterized in that: The polyetherimide solution is an N-methylpyrrolidone solution with a mass concentration of 100 to 150 mg / mL.

5. The method for preparing a polyetherimide-based high-temperature energy storage composite dielectric material according to claim 1, characterized in that: The ferroelectric polymer is polyvinylidene fluoride PVDF, polyvinylidene fluoride-co-hexafluoropropylene P (VDF-HFP) or Kramar terpolymer P (VDF-TrFE-CFE).

6. The method for preparing a polyetherimide-based high-temperature energy storage composite dielectric material according to claim 1, characterized in that: The ferroelectric polymer solution is prepared as follows: The ferroelectric polymer is added into N-methylpyrrolidone solvent and stirred at a temperature of 50 to 80° C. for 8 to 10 hours to obtain a ferroelectric polymer solution with a concentration of 180 to 210 mg / mL.

7. The method for preparing a polyetherimide-based high-temperature energy storage composite dielectric material according to claim 1, characterized in that: The nano core-shell filler is added to the N-methylpyrrolidone solvent, and ultrasonic treatment is performed using a cutting-edge ultrasonic device, with an ultrasonic power of 600-700W and an ultrasonic time of 10-15h.

8. The method for preparing a polyetherimide-based high-temperature energy storage composite dielectric material according to claim 1, characterized in that: The preparation of the composite dielectric film includes uniformly coating the composite dielectric solution on a glass substrate by a casting method, keeping it warm in an oven preheated to 70°C for 12 to 15 hours, then heating it to 100 to 120°C and keeping it warm for 5 to 8 hours, and then keeping it warm at 150 to 160°C and 200 to 210°C for 12 to 15 hours respectively to obtain the composite dielectric film.

9. A polyetherimide-based high-temperature energy storage composite dielectric material prepared by the method according to any one of claims 1 to 8.

10. Application of the polyetherimide-based high-temperature energy storage composite dielectric material as claimed in claim 9 in high-temperature polymer materials for smart grids, distributed energy and hybrid vehicles.

Citation Information

Patent Citations

  • Core-shell structure filler, preparation method thereof and application of core-shell structure filler in polyetherimide-based energy storage composite dielectric film

    CN117757147A

  • Core shell structure powder and method for preparing polymer-based dielectric composite material thereof

    CN105367959A

  • Preparation method of nano composite film

    CN118388813A

  • Composite film and preparation method and application thereof

    CN119081402A

  • Method for manufacturing film for film capacitor, and film for film capacitor

    JP2011126104A